A critical evaluation of the preferential procurement strategy and enterprise development strategy of a major motor manufacturer in the Eastern Cape - Makapela, Nobuntu Unathi B (Rhodes University, Faculty of Commerce, Rhodes Business School, 2005)
This research is born out of recognition of the challenges Black Economic Empowerment (BEE) in the private sector faces in South Africa, with preferential procurement being one of the components of South Africa's Broad Based Black Economic Empowerment Strategy. Over the past years, South Africa has witnessed the birth of a new economy, one that allows for investment in its people, makes provision for sustainable growth through skills transfer and development, and ensures economic empowerment. The focus of this research is the Preferential Procurement strategy implemented at DaimlerChrysler South Africa (DCSA) as part of its overall Black Economic Empowerment strategy, the perceptions and expectations of how the current BEE preferential procurement strategy should work versus the perceived performance of how it is working. An official definition of Black Economic Empowerment is presented in the study, followed by barriers to growth of BEE suppliers. The aim of defining Black Economic Empowerment is to provide a good reference point against which an organization like DaimlerChrysler can assess the implementation of its preferential procurement programmes. Having discussed the above, there will be a reflection on government scorecard and a brief discussion of the two charters namely, mining and financial services charter. The study also presents the following requirements for a successful BEE corporate strategy: Strategic intent; External Balanced Scorecard; Financial Assistance; Skills development; Communication. A research methodology for conducting this study and data analysis is presented, followed by limitations of the study and recommendations for further research. It is expected that the knowledge gained from this study will help to I. Demonstrate the need to change perceptions and behaviour regarding Black Economic Empowerment. 2. Assist procurement officials to include BEE objectives into their procurement strategy. 3. Identify policy implications and assist in improving DCSA's Black Economic Empowerment Procurement strategy.
Keywords: DaimlerChrysler; Employee empowerment -- South Africa -- Eastern Cape; Black people -- South Africa -- Economic conditions; Business enterprises, Black -- South Africa -- Eastern Cape; Economic development -- South Africa -- Eastern Cape